Perlindungan Hukum terhadap Advokat dan Klien dalam Penyelesaian Perkara Perdata - I Putu Esha Wiryana Putra; I Made Arjaya; NI Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
The relationship between lawyers and clients that arises as a result of the legal relationship that is established often leads to legal disputes. The dispute can result in losses for both parties, while this legal arrangement regarding the issue has not fully accommodated the needs of advocates and clients. The purpose of this study is to analyze the rights and obligations of advocates and clients and dispute resolution that can be taken by advocates and clients. This type of research is a normative legal research, using a statutory approach. The results of this study indicate that the regulation regarding the rights and obligations of advocates is regulated in Law Number 18 of 2003 concerning Advocates and the code of ethics for advocates. Meanwhile, the rights and obligations of clients, as a broader understanding of consumers, are regulated in the Law on Advocates and the Civil Code. If there is a dispute due to a legal relationship that arises between an advocate and a client, the legal settlement can be through the Advocate Code of Ethics Body, the General Court of Justice and Arbitration, Mediation and other alternative dispute resolutions.